Modeling Pancreatic Endocrine Cell Adaptation and Diabetes in the Zebrafish - Maddison, Lisette A.; Chen, Wenbiao (Frontiers in Endocrinology, 2017)
Glucose homeostasis is an important element of energy balance and is conserved in organisms from fruit fly to mammals. Central to the control of circulating glucose levels in vertebrates are the endocrine cells of the pancreas, particularly the insulin producing β-cells and the glucagon producing α-cells. A feature of α- and β-cells is their plasticity, an ability to adapt, in function and number as a response to physiological and pathophysiological conditions of increased hormone demand. The molecular mechanisms underlying these adaptive responses that maintain glucose homeostasis are incompletely defined. The zebrafish is an attractive model due to the low cost, high fecundity, and amenability to genetic and compound screens and mechanisms governing the development of the pancreatic endocrine cells are conserved between zebrafish and mammals. Post development, both β- and α-cells of zebrafish display plasticity as in mammals. Here we summarize the studies of pancreatic endocrine cell adaptation in zebrafish. We further explore the utility of the zebrafish as a model for diabetes, a relevant topic considering the increase in diabetes in the human population.